On Skeletochronology of Asian grass frog Fejervarya limnocharis (Gravenhorst, 1829) from Java to support management conservation - Ni Luh Putu Rischa Phadmacanty; Amir Hamidy; Gono Semiadi (Treubia, 2018)
Asian grass frog Fejervarya limnocharis is being utilized as pets, for laboratory experiments, for a mixture of traditional medicine and for cuisine. The harvest of F. limnocharis in high volume can threat its population. Biological data such as the age when the specimens are harvested is valuable information to manage the harvesting system in sustainable way. We conducted the skeletochronology technique using paraffin methods and hematoxylin staining from 69 samples (46 males, 21 females, 2 juveniles). The results showed that the age harvested male ranged from 1 to 3 years old, while the female ranged from 2 to 3 years old. The snout-vent length (SVL) of harvested specimens ranges between 39.84−52.37 mm for both sexes. We propose an intervention in the harvesting system by limitation of the size for harvested specimens to at least 46 mm. In this minimum size, individuals of F. limnocharis have reproduced several times and have contributed to the population in the wild.